Validity and reliability of the Questionnaire for Compliance with Standard Precaution - Marília Duarte Valim; Maria Helena Palucci Marziale; Miyeko Hayashida; Fernanda Ludmilla Rossi Rocha; Jair Lício Ferreira Santos (Universidade de São Paulo, 2015)
ABSTRACT OBJECTIVE : To evaluate the validity and reliability of the Questionnaire for Compliance with Standard Precaution for nurses. METHODS : This methodological study was conducted with 121 nurses from health care facilities in Sao Paulo's countryside, who were represented by two high-complexity and by three average-complexity health care facilities. Internal consistency was calculated using Cronbach's alpha and stability was calculated by the intraclass correlation coefficient, through test-retest. Convergent, discriminant, and known-groups construct validity techniques were conducted. RESULTS : The questionnaire was found to be reliable (Cronbach's alpha: 0.80; intraclass correlation coefficient: (0.97) In regards to the convergent and discriminant construct validity, strong correlation was found between compliance to standard precautions, the perception of a safe environment, and the smaller perception of obstacles to follow such precautions (r = 0.614 and r = 0.537, respectively). The nurses who were trained on the standard precautions and worked on the health care facilities of higher complexity were shown to comply more (p = 0.028 and p = 0.006, respectively). CONCLUSIONS : The Brazilian version of the Questionnaire for Compliance with Standard Precaution was shown to be valid and reliable. Further investigation must be conducted with nurse samples that are more representative of the Brazilian reality. The use of the questionnaire may support the creation of educational measures considering the possible gaps that can be identified, focusing on the workers' health and on the patients' safety.